Partial anomalous hepatic venous drainage into left-sided atrium with right isomerism: A case report with review of literature - Kumar, Ishan; Bhatia, Anmol; Sodhi, Kushaljit S; Khandelwal, Niranjan (Indian Journal of Radiology and Imaging, 2017)
Right isomerism, also known as Ivemark syndrome, is an unusual degree of symmetry of some of the abdominothoracic viscera reflecting bilateral right-sidedness. We report an exceedingly rare occurrence of anomalous drainage of the left hepatic vein to the left-sided atrium in a patient of right isomerism. With this case report, we further endorse that the isomerism of atrium might extend beyond the appendages, a view that has been long dismissed by the existing literature.
Keywords: Anomalous; drainage; hepatic; left atrium; venous